EFEKTIVITAS PERATURAN PRESIDEN TERKAIT PENGADAAN, PENYALURAN DAN HARGA JUAL ECERAN BAHAN BAKAR MINYAK BERSUBSIDI DI KOTA BATAM - SIANTURI, GABRIEL SHAFTO ARA ANGGITO; Jamba, Padrisan (LPPM Universitas Putera Batam, 2023)
The provision, distribution, and retail price of subsidized fuel oil are crucial issues inefforts to address energy price instability in Batam City. The enactment of presidentialregulations to govern these aspects is expected to enhance the effectiveness of the fuelsubsidy policy. This study aims to evaluate the effectiveness of the implementation ofpresidential regulations regarding the provision, distribution, and retail price of subsidizedfuel oil in Batam City. The research method employed is descriptive analysis, gatheringdata from primary and secondary sources. The research findings indicate that despite theimplementation of presidential regulations, there are still several obstacles hampering itseffectiveness. Factors such as inadequate infrastructure, consistent scarcity of fuel oilstocks, and logistical constraints pose significant challenges in the provision anddistribution of subsidized fuel oil. Moreover, the retail price of subsidized fuel oil remainsvulnerable to market fluctuations, and some business actors continue to exploit thesubsidy policy for personal gains. The proposed recommendations include improvingsupporting infrastructure, diversifying sources of subsidized fuel oil, and enhancingoversight of regulation implementation. Collaborative efforts among the government,industry, and society are essential to achieve the goal of an effective fuel subsidy policy inBatam City